2023
DOI: 10.1021/jacs.3c05171
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Selectivity Roadmap for C–N Electro-Coupling on MXenes

Abstract: Electrochemical coupling between carbon and nitrogen species to generate high-value C–N products, including urea, presents significant economic and environmental potentials for addressing the energy crisis. However, this electrocatalysis process still suffers from limited mechanism understanding due to the complex reaction networks, which restricts the development of electrocatalysts beyond trial-and-error practices. In this work, we aim to improve the understanding of the C–N coupling mechanism. This goal was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Prior theoretical studies have indicated that bond formation reactions are not favored on strong binding metals . This pattern is particularly important for reactions occurring via the Langmuir–Hinshelwood mechanism due to the simultaneous weakening of two strong adsorbate–surface interactions . On the other hand, this trend is expected to be less important for reactions via the Eley–Rideal mechanism as it involves only weakening one adsorbate–surface interaction.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Prior theoretical studies have indicated that bond formation reactions are not favored on strong binding metals . This pattern is particularly important for reactions occurring via the Langmuir–Hinshelwood mechanism due to the simultaneous weakening of two strong adsorbate–surface interactions . On the other hand, this trend is expected to be less important for reactions via the Eley–Rideal mechanism as it involves only weakening one adsorbate–surface interaction.…”
Section: Resultsmentioning
confidence: 97%
“…Prior theoretical studies have indicated that bond formation reactions are not favored on strong binding metals . This pattern is particularly important for reactions occurring via the Langmuir–Hinshelwood mechanism due to the simultaneous weakening of two strong adsorbate–surface interactions .…”
Section: Resultsmentioning
confidence: 98%
“…Huang et al used machine learning to reveal a strong correlation between the decomposition barrier of Na 2 S and the number of outermost electrons of the metal element . Based on the valence electrons and electronegativity of MXene surface and subsurface atoms, several potential MXene catalysts with good C–N coupling performance were discovered …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the adsorption strength of reaction intermediates on bimetallic alloys is mainly affected by geometric (e.g., coordination number, interatomic distances) and electronic (atomic combinations) effects. Thanks to the advances in theoretical simulation techniques, now it is possible to predict activity and selectivity based on the scaling relationship between the adsorption energy of key intermediates and geometry/electronic descriptors. , For example, Xiao et al built a Gibbs free energy landscape and constructed a volcano plot to predict potential two-dimensional (2D) metal borides (MBenes) catalysts for electrochemical urea synthesis. Qiao et al revealed that the activity of the C–N coupling step is largely determined by the *CO adsorption strength, while the selectivity relies more on the coadsorption strength of *N and *CO. Zhang et al constructed a volcano plot as a function of the free energy of *NCON intermediate to predict MBenes for urea formation. Zhu et al proposed a five-step high-throughput screening method for excellent catalytic activity and a five-aspect high-throughput screening strategy for outstanding catalytic selectivity.…”
Section: Introductionmentioning
confidence: 99%